Cognitive and Family Correlates of Current Suicidal Ideation in Children with Bipolar Disorder - Weinstein, Sally M. (J Affect Disord, 2014)
BACKGROUND: Suicidality among youth with bipolar disorder is an extreme, but largely unaddressed, public health problem. The current study examined the psychosocial characteristics differentiating youth with varying severities of suicidal ideation that may dictate targets for suicide prevention interventions. METHODS: Participants included 72 youth aged 7–13 (M = 9.19, SD = 1.61) with DSM-IV-TR bipolar I, II, or NOS and a parent/caregiver. Current suicidal ideation and correlates were assessed at intake, including: demographics and clinical factors (diagnosis, symptom severity, psychiatric comorbidity); child factors (cognitive risk and quality of life); and family factors (parenting stress, family cohesion, and family rigidity). RESULTS: Current ideation was prevalent in this young sample: 41% endorsed any ideation, and 31% endorsed active forms. Depression symptoms, quality of life, hopelessness, self-esteem, and family rigidity differentiated youth with increasing ideation severity. Separate logistic regressions examined all significant child- and family-level factors, controlling for demographic and clinical variables. Greater family rigidity and lower self-esteem remained significant predictors of current planful ideation. Diagnosis, index episode, comorbidity, and mania severity did not differentiate non-ideators from those with current ideation. LIMITATIONS: Limitations include the small sample to examine low base-rate severe ideation, cross-sectional analyses and generalizability of findings beyond the outpatient clinical sample. CONCLUSIONS: Findings underscore the importance of assessing and addressing suicidality in preadolescent youth with bipolar disorder, before youth progress to more severe suicidal behaviors. Results also highlight child self-esteem and family rigidity as key treatment targets to reduce suicide risk in pediatric bipolar disorder.